Analyses of fungal community by Illumina MiSeq platforms and characterization of Eurotium species on Liupao tea, a distinctive post-fermented tea from China. (September 2017) - Mao, Yan; Wei, BaoYao; Teng, JianWen; Huang, Li; Xia, Ning
Abstract: Liupao tea is a distinctive Chinese dark tea obtained by indigenous tea fermentation facilitated by the symbiotic association of bacteria and fungi. The composition of fungal community in 4 Liupao tea samples stored for several years under natural microbial fermentation was evaluated by MiSeq sequencing. Taxonomic analysis revealed 3 phyla, 6 families, 8 genera. The genera Eurotium and Aspergillus were dominant fungi in almost all the samples. A total of 85 strains found in 41 other tea samples were species of Eurotium . amstelodami, Eurotium . niveoglaucum, Eurotium . repens, Eurotium . rubrum, Eurotium . tonophilum and Eurotium . cristatum by culture-dependent method. Of these species, E . repens, E . rubrum and E . tonophilum have not been previously associated with Liupao tea. This report is the first to reveal fungal flora composition using Illumina-based sequencing and provide useful information for relevant studies on the isolation of Eurotium species in Liupao tea. The predominant molds are Eurotium species, and the comparison of fungal diversity in dark teas is worth considering. The taxonomic analysis of the microbial community would also aid the further study of functional genes and metabolic pathways of Liupao tea fermentation. Graphical abstract: Highlights: The first study to characterise the microbial community in aged Liupao tea by Next-generation sequencing. Genus Eurotium were obtained from all Liupao tea aging fermentation. Eurotium species were monitored by the multilocus sequence typing method Mycobiota characterization is required to avoid the contamination from potentially toxic fungi.